2018
DOI: 10.1097/mjt.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Controlling Nutritional Status in Patients Undergoing Curative Thoracoscopic Esophagectomy for Esophageal Cancer

Abstract: It is now clear that cancer survival is determined not only by tumor pathology but also by host-related factors, in particular, nutritional status and systemic inflammation. It is desirable that the essential properties of any scale designed or intended to be used for the prediction of survival are simple, convenient, and objective. In this study, we retrospectively reviewed the database of patients who underwent curative surgery for esophageal cancer in our department to evaluate controlling nutritional statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 18 publications
0
56
1
Order By: Relevance
“…Consequently, the duration of hospital stay in patients with moderate or severe malnutrition was significantly longer compared to well-nourished or slightly malnourished patients [30]. Similarly, Hirahara et al [31] and Toyokawa et al [32] demonstrated that CONUT was significantly associated with cancer death and poorer disease-free survival in patients with resectable esophageal squamous cell carcinoma. NRI is another tool used for the assessment of malnutrition based on serum albumin concentration and weight loss.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outmentioning
confidence: 93%
“…Consequently, the duration of hospital stay in patients with moderate or severe malnutrition was significantly longer compared to well-nourished or slightly malnourished patients [30]. Similarly, Hirahara et al [31] and Toyokawa et al [32] demonstrated that CONUT was significantly associated with cancer death and poorer disease-free survival in patients with resectable esophageal squamous cell carcinoma. NRI is another tool used for the assessment of malnutrition based on serum albumin concentration and weight loss.…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outmentioning
confidence: 93%
“…In addition, multivariate analysis showed that the CONUT score was an independent risk factor for CSS in surgically resected colorectal cancer patients. Hirahara et al 13) also presented that the CONUT score was a significant predictor of CSS in surgically resected esophageal cancer patients and the CONUT score was a significant predictor of CSS in patients with surgically resected esophageal cancer in the multivariate analysis. We also recently have shown that DFS, CS, and OS in patients with early-staged NSCLC with an abnormal CONUT score were significantly shorter than those in patients with a normal CONUT score and the CONUT score was an independent predictive factor of DFS, CSS, and OS.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have shown NLR to be predictive of outcomes in ECs 2529. However, the cutoff values for elevated NLR varied in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cutoff values for elevated NLR varied in these studies. In these studies investigating NLR in EC, the cutoff value was mean/median value25,26 or was determined with ROC analysis27,28 or accepted as the cutoff value as in previous studies 29,30. The patients were classified according to a cutoff value (3.5) accepted as in a previous study by Feng et al,24 whereas in the present study, the cutoff value was determined by using the ROC analysis and it was calculated to be 2.97 by using a time-dependent ROC curve.…”
Section: Discussionmentioning
confidence: 99%